Performa Termal Kondensor Udara pada Wind Tunnel: Evaluasi Perpindahan Panas - Priyadi, M. Untung Zaenal; Saleh, Yasya Khalif Perdana; Fikri, Muhammad Luqman Saiful; Muddhar Fathkhur Rohman; Leo Saputra (Universitas Nusa Putra, 2024)
Heat transfer in air condenser systems is a critical aspect in various industrial applications, especially refrigeration and air conditioning systems. The thermal efficiency of condensers is greatly influenced by airflow characteristics, but airflow velocity optimization remains a challenge due to the trade-off between improved heat transfer and energy consumption. Although previous research has examined various aspects of condenser design, there is still a need to explore the optimal limit of airflow velocity that can maximize thermal efficiency without excessively increasing system workload. This study aims to evaluate the thermal performance of an air condenser in a wind tunnel, focusing on the effects of airflow velocity variations on heat transfer rate and thermal efficiency. The experimental method uses a wind tunnel with dimensions of 280x28x28 cm, equipped with a precise temperature and flow velocity measurement system. The flow velocity was varied from 0.8 to 1.8 m/s. The results showed a significant increase in the heat transfer coefficient (h) and heat transfer rate (Q) as the flow velocity increased. Analysis of Reynolds and Nusselt numbers revealed the transition of the flow from laminar to turbulent, which contributed to the increase in heat transfer efficiency. Comparison of experimental results with simulations showed good agreement in the middle velocity range, but there were deviations at extreme velocities. In conclusion, increasing the airflow velocity proved effective in improving the thermal performance of the condenser, but further optimization is required to balance the thermal efficiency with the energy consumption of the system.